The Effectiveness of E-Government Implementation in Encouraging Community Participation in The Local Development Planning Process in Fef District, Tambrauw Regency - Penina Fakdawer; Indra Kertati; Charis Charistiani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
UMKM Digital transformation in local governance is an important instrument in realizing the principles of good governance, especially in regions with complex geographical challenges. This study aims to analyze the effectiveness of e-government implementation at the district level in encouraging community participation in the local development planning process, using a case study of the Fof District Office, Tambrauw Regency. The methods used were descriptive qualitative through field observations, in-depth interviews with district officials and community leaders, and analysis of development documents. The data was analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the implementation of e-government in Fef District is in a transition phase. Bureaucratic digitization improves administrative efficiency and transparency of public information. However, its effectiveness in expanding community participation is still low. The main obstacles include limited telecommunications infrastructure in several villages and low community digital literacy. As a result, participation in Musrenbang remains dominated by conventional mechanisms, while digital platforms serve primarily as a means of one-way reporting. This study emphasizes that the success of digital transformation depends on the readiness of infrastructure and community capacity, so a hybrid approach that integrates technology with local wisdom is needed to strengthen participation in regional development.